Responses and response evaluation of immune checkpoint inhibitors in lymphoma - Anagnostou, Theodora; Ansell, Stephen M. (Annals of Lymphoma, 2017)
The survival and growth of lymphoma cells relies on suppression of antitumor immunity through interactions between the tumor microenvironment and lymphoma cells. These are mediated by a network of inhibitory and stimulatory receptors that deliver signals as part of the maintenance of peripheral tolerance. The most studied pathway is the B7-1/B7-2:CD28/CTLA-4 (cytotoxic T-lymphocyte-associated protein 4) pathway. Different molecules of this pathway are upregulated in lymphoma contributing to T-cell exhaustion and anergy and allowing tumor escape from the immune mechanisms. Additional activating and inhibitory signals modulate this pathway, and the inhibitory signal provided by the PD-L1/PD-L2:PD-1 (programmed cell death 1) axis has been found to be particularly important. PD-1 inhibitors promote immune activation and have recently been approved for the treatment of classical Hodgkin lymphoma (HL) that has relapsed after autologous stem-cell transplantation (SCT) and treatment with brentuximab vedotin. The clinical trials that led to their approval showed objective response (OR) rates over 70% and responses were durable. Less impressive responses have been described in non-HL due to the differences in the biology and composition of tumor microenvironment of these two types of lymphoma. Recently the response criteria were redesigned to reflect immune changes in the tumors caused by the medications used. Ongoing and future studies are focusing on the development of biomarkers for response assessment.